Toxicosis In Helicobacter Pylori Infection - A Hypothesis - Belascu, Mihai (Medicine and Pharmacy Reports, 2014)
Background and aim. We present a new clinical entity in relation to the Helicobacter pylori infection characterized by complex and varied clinical extradigestive manifestations. Clinical findings such as asthenia, adynamia, sleep disorders, hair and nails modifications, digestive symptoms and heart rhythm disorders describe the clinical aspect of toxicosis associated with Helicobacter pylori infection. Methods. The clinical presentation and therapy of patients with Helicobacter pylori infection were analyzed. Results. Combined drug therapy: antibiotics + proton pump inhibitors + colloidal bismuth compound determinate remission of the symptoms in the first 3 to 5 days. The characteristic of the relation between Helicobacter pylori and the mucus-epithelial cell complex, the properties of the bacterial cell components, and the inflammatory and immunological response targeting other organs describe the immuno pathological outbreak of Helicobacter pylori. Conclusion. We support the term of toxicosis associated with Helicobacter pylori infection in selected cases.